Development of STREAM-Based Learning Media to Improve Students' Science Literacy on The Matter Forms of Substances and Its Changes - Arifani, Lathifa Izza; Isnaeni*, Wiwi; Ellianawati, Ellianawati; Khulafa, Faris Nur (Jurnal Pendidikan Sains Indonesia, 2024)
Science learning in the merdeka curriculum expects students not only to understand concepts, but to be able to apply science concepts in everyday life. The results of TIMSS and PISA state that the science literacy ability of Indonesian students is still very low. Through initial observations and interviews showed that the use of IT-based learning media and the involvement of students in the science learning process is still lacking. Science, technology, religion, engineering, art, and mathematic (STREAM) approach is useful to build a meaningful learning. This research aims to develop STREAM-based learning media to improve students' science literacy. The method used is RD with a model define, design, development and disseminate (4D). The data analysis technique uses SPSS to perform normality tests and independent t-tests. The increase in variables is measured by N-Gain. the expert validity analysis test obtained a material validity value of 0.93, media validity of 0.94, and language validity of 0.95. The final validity value of the STREAM-based learning media was 0.94 with valid criteria. The analysis of student's responses to the readability of STREAM-based learning media obtained 92.5% with very good criteria. The N-Gain test result in experimental group obtained a score of 0.72 in the high category higher than the control group which obtained a score of 0.37 in the medium category. Based on these results, STREAM-based learning media appears to be feasible and could contribute to enhancing students' science literacy skills related to the material forms of substances and its changes